Production and characterisation of cellulase from solid state fermentation of rice straw by Trichoderma harzianum SNRS3 - Rahnama, Nooshin; Md. Shah, Umi Kalsom; Foo, Hooi Ling; Abdul Rahman, Nor Aini; Ariff, Arbakariya (Universiti Putra Malaysia Press, 2016)
Research on production and the use of cellulase and xylanase by commercial microbial strains is widely reported. However, research on production of cellulase and xylanase by local isolates of Trichoderma harzianum known as potential cellulase producers is still very limited. T. harzianum SNRS3 was used for cellulase and xylanase production from rice straw under solid state fermentation. Our study revealed that unlike Trichoderma sp. that is normally associated with low amounts of β-glucosidase, insufficient to perform an efficient hydrolysis, T. harzianum SNRS3 could be considered as a potential β-glucosidase producer, but not an efficient xylanase producer. As a result of storage of the crude cellulase at room temperature, β-glucosidase activity only decreased to above 80% of its original activity at the end of the 3rd week of storage. The crude cellulase produced by T. harzianum SNRS3 could be industrially applied as the enzyme is still highly active at 60°C and over a wide range of acidic pH.